Strategi Pemasaran Dan Promosi UMKM Barokah 717 Desa Ambulu Guna Memperluas Pangsa Pasar - Ersa Falevi Anggraini; Sugito Sugito (Universitas Muhammadiyah Manado, 2023)
Product marketing and promotion is one alternative that can be done by MSMEs to expand their business in the market aspect. UMKM Barokah 717 is a business engaged in food production located in Ambulu Village, Sumberasih District, Probolinggo Regency. These MSMEs in the marketing stage are still doing around the environment with the word of mouth method and consumers from outside the city are still few. In this community service program using technology, product marketing and branding can be done with the help of social media in the current era. The research method is descriptive qualitative using observation and interview techniques in collecting research data. Based on the results of the study, MSMEs already have accounts but are rarely managed, there are product photos but do not attract out-of-town consumers, need to redesign logos, and make banners to promote the business